Analisis Tingkat Pendapatan Usaha Ternak Sapi Potong Sistem Gaduhan Di Distrik Arso Kabupaten Keerom Provinsi Papua - Nuhon, Kornelius Liat; Hetharia, Lucas Filips (Jurnal Pertanian Terpadu Santo Thomas Aquinas, 2022)
This study aims to determine the level of income from the gaduhan system business of beef cattle run by beneficiary breeders in Arso District, Keerom Regency, Papua Province.The method used is a survey method with data collection techniques through direct observation and interviews with the help of flat questions to 10 farmer respondents who were deliberately selected from the 31 population of beef cattle breeders in the gaduhan system in Arso District in 2019 for approximately one month starting from April to May 2021. The collected data is processed and analyzed using cost analysis formulas. The results showed that the gaduhan system business of beef cattle in Arso District, Keerom Regency, Papua Province provides a sufficient level of income for farmers because the difference between revenue and production costs is positive, which average of Rp. 5.955.103,- Thus, the effort to raise beef cattle with the gaduhan system in the Arso District, Keerom Regency, PapuaProvince, especially in the 2019 aid package, has provided economic benefits because it contributes to income to improve the welfare of the farmers family